Peningkatan Pengetahuan Ibu Menyusui Tentang Pentingnya ASI Eksklusif Melalui Edukasi Kesehatan - Yuliana, Dewi; Lestari, Yuli; Subardiah, Ida (ANDASIH Jurnal Pengabdian kepada Masyarakat, 2025)
Exclusive breastfeeding plays a vital role in supporting infant growth, development, and immunity. However, the exclusive breastfeeding rate in Indonesia has not yet reached the national target due to mothers’ limited knowledge about its benefits and proper breastfeeding techniques. This community service activity aimed to improve mothers’ knowledge of the importance of exclusive breastfeeding through health education. The method applied was a participatory education approach involving counseling, discussions, and the distribution of educational media to 25 breastfeeding mothers in the working area of Puskesmas Simpur, Bandar Lampung City. Evaluation was conducted using pre-test and post-test questionnaires to measure knowledge levels. The results showed an increase in the average knowledge score from 65.4 to 88.6, indicating a 35.4% improvement. Health education proved effective in enhancing mothers’ knowledge and awareness regarding the importance of exclusive breastfeeding. It is expected that similar activities will be carried out continuously by involving families and health cadres to support the success of exclusive breastfeeding programs in the community. Keywords: exclusive breastfeeding, breastfeeding mothers, health education, knowledge